Effects of acute physical exercise on oxidative stress and inflammatory status in young, sedentary obese subjects - Accattato, Francesca (PLoS One, 2017)
Circulating oxidative stress and pro-inflammatory markers change after regular physical exercise; however, how a short session of acute physical activity affects the inflammatory status and redox balance in sedentary individuals is still unclear. Aim of this study is to assess antioxidant and inflammatory parameters, both at rest and after acute exercise, in sedentary young men with or without obesity. Thirty sedentary male volunteers, aged 20–45 (mean age 32 ± 7 years), were recruited, divided into 3 groups (normal weight: BMI < 25 kg/m(2); overweight to moderate obesity: 25–35 kg/m(2); severe obesity: 35–40 kg/m(2)), and their blood samples collected before and after a 20-min run at ~ 70% of their VO(2max) for the measurement of Glutathione Reductase, Glutathione Peroxidase, Superoxide Dismutase, Total Antioxidant Status (TAS) and cytokines (IL-2, IL-4, IL-6, IL-8, IL-10, IL-1α, IL-1β, TNFα, MCP-1, VEGF, IFNγ, EGF). Inter-group comparisons demonstrated significantly higher Glutathione Reductase activity in severely obese subjects in the post-exercise period (P = 0.036), and higher EGF levels in normal weight individuals, either before (P = 0.003) and after exercise (P = 0.05). Intra-group comparisons showed that the acute exercise stress induced a significant increase in Glutathione Reductase activity in severely obese subjects only (P = 0.007), a significant decrease in MCP-1 in the normal weight group (P = 0.02), and a decrease in EGF levels in all groups (normal weight: P = 0.025, overweight/moderate obesity: P = 0.04, severe obesity: P = 0.018). Altogether, these findings suggest that in sedentary individuals with different ranges of BMI, Glutathione Reductase and distinct cytokines are differentially involved into the adaptive metabolic changes and redox responses induced by physical exercise. Therefore, these biomarkers may have the potential to identify individuals at higher risk for developing diseases pathophysiologically linked to oxidative stress.